Asymptotic Estimates for Second Kind Generalized Stirling Numbers - Cristina B. Corcino; Roberto B. Corcino (Journal of Applied Mathematics)
Asymptotic formulas for the generalized Stirling numbers of the second kind with integer and real parameters are obtained and ranges of validity of the formulas are established. The generalizations of Stirling numbers considered here are generalizations along the line of Hsu and Shuie's unified generalization.